2012
DOI: 10.1177/1557988311431628
|View full text |Cite
|
Sign up to set email alerts
|

Condom Use by Partner Type Among Military and Police Personnel in Peru

Abstract: The aim of this study was to analyze the rates of condom use among military and police populations in Peru, focusing on differences in use by type of partner. A Knowledge Attitudes and Practices survey was conducted among 6,808 military and police personnel in 18 Peruvian cities between August–September 2006 and September–October 2007. A total of 90.2% of the survey respondents were male; mean age was 37.8 years and 77.9% were married/cohabiting. In all, 99.5% reported having had sex; 89% of the participants h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…This is in line with the study done in north-western Ethiopia among HIV/AIDS patients receiving antiretroviral therapy. 28 Unlike the other study done in Gamo-Gofa Zone, South West Ethiopia, 33 Ethiopian Military personals, 21 and Ethiopia Harreri police force, 7 this study failed to demonstrate the significant association between age and consistent condom use. This might be due to most of the study participants found under the same age categories.…”
Section: Discussioncontrasting
confidence: 71%
“…This is in line with the study done in north-western Ethiopia among HIV/AIDS patients receiving antiretroviral therapy. 28 Unlike the other study done in Gamo-Gofa Zone, South West Ethiopia, 33 Ethiopian Military personals, 21 and Ethiopia Harreri police force, 7 this study failed to demonstrate the significant association between age and consistent condom use. This might be due to most of the study participants found under the same age categories.…”
Section: Discussioncontrasting
confidence: 71%
“…Other studies evaluating the potential use of harm-reduction techniques among HIV-infected and HIV-uninfected MSM and TGW in Peru have found no evidence of serosorting, discussion of HIV infection status, or other partner-specific strategies to control risk of HIV/STI transmission [4] , [6] . Epidemiologic studies from across Latin America have reported a higher overall prevalence of UAI with stable compared with casual partners among MSM and TGW, though we are not aware of any studies in the region that have conducted partner-level analyses of the association between UAI and partner type [2] , [3] , [22] , [23] . Detailed knowledge of how partner type influences sexual risk behavior among MSM and TGW in Latin America will contribute to the development of culturally- and epidemiologically-specific interventions to control the spread of HIV and STIs in this population.…”
Section: Introductionmentioning
confidence: 94%
“…30 Usually dichotomizations by other authors consider ''consistent'' use as use in 100% of sexual contacts; any other value is considered ''inconsistent.'' Military populations may be ideal for educational strategies that minimize risky behaviours.…”
Section: Risk Behaviourmentioning
confidence: 99%
“…Although some researchers prefer to dichotomize the variable ''condom use'' in favour of allowing normal data distribution and therefore a less complicated analytic method 29 a variable divided in six strata was used for this manuscript, to be described as thoroughly as possible. 30 Usually dichotomizations by other authors consider ''consistent'' use as use in 100% of sexual contacts; any other value is considered ''inconsistent.'' Military populations may be ideal for educational strategies that minimize risky behaviours.…”
Section: Risk Behaviourmentioning
confidence: 99%